Jaringan Komunikasi Dan Peran Perempuan Dalam Mempertahankan Budaya Rudat (Studi Pada Masyarakat Desa Negeri Katon, Kecamatan Negeri Katon, Lampung Selatan) - A. Gustina; A.V.S. Hubeis; S. Riyanto (Jurnal Komunikasi Pembangunan, 2008)
The objectives of the research were (1) to describe the configuration of communication network related to thedissemination of information about the rudat culture and to examine its specific roles in the network (2) to examinethe role of women in the process of dissemination of information about the rudat culture and the ceremony in DesaNegeri Katon, and (3) to examine the relation between the peoples communication network and the role of women inthe process of dissemination of information about the rudat culture and the ceremony in Desa Negeri Katon. TheResearch was held upon the people of Desa Negeri Katon, Kecamatan Negeri Katon, South Lampung. Primary datahad been collected by methods of survey, sociometry and indepth interview. The survey was held by sets ofquestionnaire asked to 97 respondents, the sociometry was used to analize the communication network, and theindepth interviews were used in collecting qualitative data. The intervariable relation was then analized usingstatistical test correlational coefficient rank spearman and the multilinear regression test. The results showed that 1)the structure communication network composes a mere great clique, 2) the specific roles in the network are star andneglectee, and 3) there are significant connection between its communication network with the roles of woman in theprocess of dissemination of information.